Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Kinerja Karyawan di Hotel Grandhika Iskandarsyah Jakarta Selatan - Rahmi Hermawati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Employee performance is a critical factor in achieving organizational goals, particularly in the hospitality industry, where service quality directly affects customer satisfaction and business success. Leadership style and employee motivation have been widely recognized as key determinants influencing employee performance. This study aims to examine the effect of leadership style and motivation on employee performance at the Grandhika Iskandarsyah Hotel in South Jakarta. The research employed a quantitative approach with a survey method. The population consisted of all 53 employees of the hotel, and the entire population was used as a sample through saturated sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using SPSS version 25. Analytical procedures included validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing through t-test and F-test. The results indicate that both leadership style and motivation have a significant impact on employee performance. An effective leadership style guides, directs, and facilitates employees, enhancing productivity and work quality, while motivation acts as an internal drive that encourages employees to perform optimally and remain committed to their duties. Furthermore, the interaction between leadership style and motivation creates a synergistic effect, demonstrating that optimal performance is achieved not by a single factor alone but through the combination of appropriate leadership and sufficient employee motivation. These findings highlight the importance for management to develop leadership strategies and motivational programs to improve employee performance and organizational outcomes.